Islam dan humanisme. Aktualisasi humanisme Islam di tengah krisis humanisme universal - [Tidak Terdaftar] (Pustaka Pelajar, 2007)
Islam dan humanisme. Aktualisasi humanisme Islam di tengah krisis humanisme universal